The Overview of knowledge about DHF prevention in communities coastal Kolono Konawe Selatan District - Bahar, Hartati; Muchtar, Febriana (Universitas Islam Negeri Alauddin Makassar, 2022)
Indonesia's health profile data shows that the incidence of dengue fever reaches 27.0 per 100,000 population and the province of Southeast Sulawesi has an incidence rate of 24.6 per 100,000 population, almost reaching the national average incidence rate. This study aims to obtain an overview of the knowledge of the coastal community of Kolono about knowledge about the prevention of dengue disease. This type of research is a descriptive survey with a research population of 6374 people. Sample in this study were 952 respondents spread over 12 sub-districts in Kolono District. Sampling technique is Proportional Random Sampling. The results showed that 764 respondents (80.3%) did not know the definition of dengue disease, there were 762 respondents or 80.04% who did not have good knowledge regarding the breeding grounds of the Aedes Aegypti mosquito and there were 694 respondents or 72.9% who did not know. ways to prevent dengue. It is hoped that health education will be carried out to increase public knowledge, especially ahead of the transition season to improve DHF prevention behavior in the Kolono sub-district community.